The Correlation Between Student’s Translation Ability And Reading Comprehension - Brillian Nur Zilullah; Hanafi; Kristi Nuraini (SS&H: Studies in Social Sciences and Humanities, 2025)
Reading is categorized as the receptive skills, which need to know the meaning to understand the discourse about. While reading in order to understand the meaning of what they are reading, students will be translating the English language as foreign language text to understand the text. In this instance, the ability to translate cannot be divorced from the ability to learn English, particularly the ability to read. Hence, the goal of this study is to find out how students' translation skills and reading comprehension skills relate to one another. Quantitative method is applied on this research to measure the data. It means that this quantitative research is the illustration of the fact by numerical or statistical analysis. Data was collected through test (reading comprehension and translation ability tests), and the data was analyzed using the SPSS program's Pearson correlation product moment. The findings indicate a strong relationship between students' translation skills and their reading comprehension. Students' average scores for reading comprehension and translation skills are 60.00 and 71.59, respectively. The two-tailed sig value is 0.009 less than 0.05. Thus, it can be inferred that pupils' reading comprehension and translation skills are positively correlated. In conclusion, students' reading comprehension skills and their capacity to translate news item text are significantly correlated.